Characterization of the association between cigarette smoking intensity and urinary concentrations of 2-hydroxyethyl mercapturic acid among exclusive cigarette smokers in the National Health and Nutrition Examination Survey (NHANES) 2011–2016. (3rd October 2021) - Kenwood, Brandon M.; McLoughlin, Caitlyn; Zhang, Luyu; Zhu, Wanzhe; Bhandari, Deepak; De Jesús, Víctor R.; Blount, Benjamin C.
Abstract: Background: 2-Hydroxyethyl mercapturic acid (2HEMA, N-acetyl-S-(2-hydroxyethyl)-L-cysteine) is a urinary metabolite of several volatile organic compounds including acrylonitrile and ethylene oxide, which are found in cigarette smoke. Methods: We measured 2HEMA concentrations in urine specimens collected during the National Health and Nutrition Examination Survey (2011–2016) from eligible participants aged >12 years ( N  = 7, 416). We developed two multiple linear regression models to characterize the association between cigarette smoking and 2HEMA concentrations wherein the dependent variable was 2HEMA concentrations among participants who exclusively smoked cigarettes at the time of specimen collection and the independent variables included sex, age, race/ethnicity, creatinine, diet, and either cigarettes smoked per day (CPD) or serum cotinine. Results: We detected 2HEMA in 85% of samples tested among exclusive cigarette smokers, and only 40% of specimens from non-smokers. When compared to exclusive cigarette smokers who smoked 1–9 CPD, smoking 10–19 CPD was associated with 36% higher 2HEMA ( p <  0.0001) and smoking >19 CPD was associated with 61% higher 2HEMA ( p <  0.0001). Additionally, 2HEMA was positively associated with serum cotinine. Conclusions: This study demonstrates that cigarette smoking intensity is associated with higher urinary 2HEMA concentrations and is likely a major source of acrylonitrile and/or ethylene oxide exposure.